1980
DOI: 10.1111/j.1469-8137.1980.tb00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Interactions on Vesicular‐arbuscular Mycorrhizal Infections. I. Host and Non‐host Plants Grown Together

Abstract: Summary Mycorrhizal infections formed by different endophytes were examined in 10 crop species grown separately and in pairs in sterilized and unsterile soils. No infection was observed in cabbage, kale, rape or swede (in the supposedly non‐mycorrhizal family Cruciferae) and only traces were seen in sugar beet (supposedly non‐mycorrhizal Chenopodiaceae) when these plants were grown alone. However, slight (< 5 %) infection (cortical mycelium and vesicles, but no arbuscules) developed in some when a mycorrhizal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
65
0
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(79 citation statements)
references
References 10 publications
8
65
0
2
Order By: Relevance
“…Evidence for such shoot control comes also from recent experiments on decapitated lupin seedlings by Giovannetti et al (personal communication (Trinick, 1977;Ocampo et al, 1980;Plenchette & Trouvelot, 1986). Under these conditions non-host roots still, however, show resistance to VA mycorrhizal fungi in that abortive entry points are frequent and, where roots become colonized, only intercellular hyphae form and arbuscules do not develop.…”
Section: Discussionmentioning
confidence: 86%
“…Evidence for such shoot control comes also from recent experiments on decapitated lupin seedlings by Giovannetti et al (personal communication (Trinick, 1977;Ocampo et al, 1980;Plenchette & Trouvelot, 1986). Under these conditions non-host roots still, however, show resistance to VA mycorrhizal fungi in that abortive entry points are frequent and, where roots become colonized, only intercellular hyphae form and arbuscules do not develop.…”
Section: Discussionmentioning
confidence: 86%
“…Previous observations (Ocampo et al 1980) showed that VA fungal hyphae can make some growth around the roots of 'non-hosts'. The present study suggests that these hyphae are more active in infecting roots than is fresh inoculum added at the same rate as before.…”
Section: Discussionmentioning
confidence: 97%
“…The same two soils were used as before (see Ocampo et al 1980, for full details), one from a fallow area at Woburn and the other from a maize field at Rothamsted | (Long Hoos). The Woburn soil (Tables 1, 4, 5 and 6) was sterilized with y-irradiation (1 Mrad), mixed 1:1 with sterilized sand, and inoculated with soil from stock plant cultures of either Glomus fasciculatus ' E3 ' or Gigaspora margarita which contained spores, mycelium and infected root fragments, at the rate of 5 g soil inoculum mixed with 5 g sand per 75 mm pot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant diseases caused by soilborne fungi are usually affected by the formation of mycorrhizas, and mycorrhizas are known to be effective in inhibiting the development of pathogens and reducing incidence of the disease (Dehne, 1982;Caron, 1989;Perrin, 1990). Although most plant species, including a large number of crops, can develop mycorrhizas, Cruciferae is an exceptional plant family, with few or no mycorrhizas (Ocampo et al, 1980). In some species of Cruciferae, however, the presence of an endophytic dark-septate fungus was reported and it appeared that the functional relationship between the fungus and plants might be mutualistic rather than parasitic (Vare et al, 1992).…”
Section: Introductionmentioning
confidence: 99%